Anna Matthaiou, Οικογένεια και σεξουαλικότητα: Μεταξύ παράδοσης και νεωτερικότητας (ελληνικές μαρτυρίες, 17ος–αρχές 19ου αι.) [Family and sexuality: Between tradition and modernity (Greek testimonies, 17th–early 19th centuries)] - Dialeti, Androniki (Historein, 2021)
Review of Anna Matthaiou. Οικογένεια και σεξουαλικότητα: Μεταξύ παράδοσης και νεωτερικότητας (ελληνικές μαρτυρίες, 17ος–αρχές 19ου αι.) [Family and sexuality: Between tradition and modernity (Greek testimonies, 17th–early 19th centuries)]. Athens: Melissa, 2019. 276 pp.